Pre- and post-copulatory traits working in concert: sexual dichromatism in passerines is associated with sperm morphology. (15th January 2020) - Durrant, Kate L.; Reader, Tom; Symonds, Matthew R. E.
Abstract : Passerine birds produce costly traits under intense sexual selection, including elaborate sexually dichromatic plumage and sperm morphologies, to compete for fertilizations. Plumage and sperm traits vary markedly among species, but it is unknown if this reflects a trade-off between pre- and post-copulatory investment under strong sexual selection producing negative trait covariance, or variation in the strength of sexual selection among species producing positive covariance. Using phylogenetic regression, we analysed datasets describing plumage and sperm morphological traits for 278 passerine species. We found a significant positive relationship between sperm midpiece length and male plumage elaboration and sexual dichromatism. We did not find a relationship between plumage elaboration and testes mass. Our results do not support a trade-off between plumage and sperm traits, but may be indicative of variance among species in the strength of sexual selection to produce both brightly coloured plumage and costly sperm traits.